(untitled) (Nexo Revista Científica, 2021)
The incorporation of coconut fiber in the blocks elaborated in the city of Bluefields, provided relevant information during the evaluation of its physical and mechanical properties, through the interpretation of the data obtained from the compression tests carried out at the Julio-Adolfo Laboratory of the Central American University (UCA). These blocks were analyzed in the different setting days, which are 7 and 28 days respectively, analyzing 9 blocks for each test, 6 blocks of 6" (3 with 5% of additive and 3 with 20% of additive) and 6 blocks of 4" (3 with 5% of additive and 3 with 20% of additive. The results of the tests determined that the blocks had evidence that the implementation of the fibers allows the concrete the adherence of the materials allowing the concrete to present normal cracking after the failure, but it is controlled by the fibers that prevent the prolongation of these cracks making them end there, providing ductility.